Biomass potential analysis of aquatic biomass and challenges for its use as a nonconventional substrate in anaerobic digestion plants. Issue 7 (13th June 2018) - Zehnsdorf, Andreas; Moeller, Lucie; Stabenau, Nele; Bauer, Aline; Wedwitschka, Harald; Gallegos, Daniela; Stinner, Walter; Herbes, Carsten
Abstract: Aquatic macrophytes are important components of aquatic habitats. However, the overgrowth of aquatic plants can cause severe problems for the management of bodies of water. As a result, these plants must be removed and disposed of as waste. However, the usage of this biomass as a substrate in biogas plants would appear to be more beneficial. The present study shows the advantages and barriers to the use of harvested aquatic biomass for energy production in Germany. The results cover several aspects of this issue, such as the question of biomass potential, the quality of the harvested aquatic plants, and ensiling for the purpose of conservation for anaerobic digestion. In addition, the social aspects of the de‐weeding in bodies of water are discussed.